Performance Enhancement of PEM Fuel Cells with an Additional Outlet in the Parallel Flow Field - Yan Zhang (MDPI AG, 2021)
The design of bipolar plates is critical for improving the performance of proton exchange membrane fuel cells (PEMFCs). In this research, a new additional outlet based on a PEMFC’s parallel flow field was proposed, and three different positions of outlet were designed on the target side of gas flowing in parallel channels. The results revealed that the additional outlets are able to increase the gas speed through channels near the additional outlets, which results in a lower water saturation and a more uniform distribution of oxygen concentration at the interface between the catalyst layer (CL) and gas diffusion layer (GDL). With the variation of the outlet position in the target side, it was found that the additional outlet set in the middle of the target side exhibits the highest increase of peak power density, namely, 13%. Furthermore, the optimal position of the additional outlet was proved to be suitable for PEMFCs with various active surface areas, indicating the universality of the present results in the study.